2009
DOI: 10.1111/j.1438-8677.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral biology and reproductive isolation by floral scent in three sympatric aroid species in French Guiana

Abstract: We studied the reproductive biology of three sympatric Araceae species, Anthurium sagittatum, A. thrinax and Spathiphyllum humboldtii in French Guiana. The plants flowered simultaneously and were visited by scent-collecting male euglossine bees, which were apparently their major pollinators. In total, each species was visited by 3-7 euglossine species, and 2-3 euglossine species accounted for at least 80% of all flower visits, with visits being plant species-specific. Floral scent consisted of 6-10 main compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 45 publications
1
49
0
3
Order By: Relevance
“…Rewarding mutualisms in Araceae are pollination interactions that involve a food reward, such as stigmatic exudates, small amounts of nectar (Vogel and Martens ; Diaz and Kite ), or liquid floral perfume for male euglossine bees (Hentrich et al. , ). Mating/oviposition site mutualisms involve flies or beetles that mate or oviposit in the inflorescences (Gibernau et al.…”
Section: Methodsmentioning
confidence: 99%
“…Rewarding mutualisms in Araceae are pollination interactions that involve a food reward, such as stigmatic exudates, small amounts of nectar (Vogel and Martens ; Diaz and Kite ), or liquid floral perfume for male euglossine bees (Hentrich et al. , ). Mating/oviposition site mutualisms involve flies or beetles that mate or oviposit in the inflorescences (Gibernau et al.…”
Section: Methodsmentioning
confidence: 99%
“…Schiestl & Ayasse, ; Xu et al ., ) and within other plant families (e.g. Waelti et al ., ; Hentrich et al ., ), and floral morphologies such as flower size (e.g. Schemske & Bradshaw, ), orientation and spur length (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In some plant species, it has been highly suspected or shown that floral odours are the main attractive cues. Such is the case, for example, in the very specialized interactions between fig and fig wasps (Gibernau ), orchids and male bees (Schiestl & SchlĂŒter ), yucca and yucca moth (Svensson, Pellmyr & Raguso ) or Araceae and euglossine bees (Hentrich, Kaiser & Gottsberger ). This is also the case for flowers attracting pollinators at dusk or during the night, when visual cues are poorly informative (Maia et al .…”
Section: Introductionmentioning
confidence: 99%